The neural correlates of picture naming facilitated by auditory repetition - Heath Shiree (BMC Neuroscience, 2012)
Abstract Background Overt repetition of auditorily presented words can facilitate picture naming performance in both unimpaired speakers and individuals with word retrieval difficulties, but the underlying neurocognitive mechanisms and longevity of such effects remain unclear. This study used functional magnetic resonance imaging to examine whether different neurological mechanisms underlie short-term (within minutes) and long-term (within days) facilitation effects from an auditory repetition task in healthy older adults. Results The behavioral results showed that both short- and long-term facilitated items were named significantly faster than unfacilitated items, with short-term items significantly faster than long-term items. Neuroimaging analyses identified a repetition suppression effect for long-term facilitated items, relative to short-term facilitated and unfacilitated items, in regions known to be associated with both semantic and phonological processing. A repetition suppression effect was also observed for short-term facilitated items when compared to unfacilitated items in a region of the inferior temporal lobe linked to semantic processing and object recognition, and a repetition enhancement effect when compared to long-term facilitated items in a posterior superior temporal region associated with phonological processing. Conclusions These findings suggest that different neurocognitive mechanisms underlie short- and long-term facilitation of picture naming by an auditory repetition task, reflecting both phonological and semantic processing. More specifically, the brain areas engaged were consistent with the view that long-term facilitation may be driven by a strengthening of semantic-phonological connections. Short-term facilitation, however, appears to result in more efficient semantic processing and/or object recognition, possibly in conjunction with active recognition of the phonological form.